Swallowing function after transoral surgery for laryngopharyngeal cancer. - Tsutomu Ueda; Kouhei Yumii; Yuji Urabe; Nobuyuki Chikuie; Takayuki Taruya; Takashi Kono; Takao Hamamoto; Masaya Takumida; Minoru Hattori; Takashi Ishino; Sachio Takeno (PLoS ONE, 2022)
Transoral surgery (TOS) has been widely used to treat laryngopharyngeal cancers. Although TOS is a minimally invasive procedure, postoperative complications, such as postoperative dysphagia, may occur, which can lead to a poor quality of life for patients undergoing TOS. This study aimed to investigate factors that may affect swallowing function in patients who underwent TOS for laryngopharyngeal cancers. Swallowing function of 84 patients who underwent endoscopic resection for oropharyngeal, hypopharyngeal, and supraglottic lesions was evaluated by the Functional Outcome Swallowing Scale, and predictors for postoperative dysphagia were identified. Multivariate analysis identified the following factors as independent predictors for postoperative dysphagia: Eastern Cooperative Oncology Group Performance Status (ECOG PS, p = 0.008), prior neck radiation therapy (p = 0.008), and operative time (p = 0.021). This study suggests that patients with poor ECOG PS or those who received prior neck radiation therapy should be fully assessed for preoperative swallowing function. In the future, we would like to clarify the criteria for preoperative swallowing evaluation to create a system that can identify patients suitable for TOS.